Building Effective Performance Motivation for Educators at MIN 2 Bandung City - Asri Sulastri; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The focus of this research is how to describe the motivation to improve the performance of educators at MIN 2 Bandung City. The method used is a descriptive method with a quantitative approach which is further supported by a questionnaire as a data collection tool. The location of this research is Madrasah Ibtidaiyah Negeri 2 Bandung City with a sample of educators who served as research respondents. The results of this study illustrate that motivation has a sufficient influence on educator performance. As many as 50% of educators feel motivated, and there are 4.5% of educators who feel unmotivated to perform well. Regarding personal satisfaction with educator performance, 50% feel satisfied, 22.7% feel very satisfied, but there are 4.5% of educators who feel dissatisfied with their performance.